The Geographic Analysis of Problematic Auctioned Residential Properties - Yahya, Zahiriah; Daud, Md Nasir; Esha, Zulkifli; Mohd Adnan, Yasmin; Wai Seen, Chan (Journal of Surveying, Construction and Property, 2013)
Of late, there has been a significant increase in the number of residential properties in Malaysia remaining unsold after repeated sales by auction. This growth in the incidence of what can be termed as problematic auctioned properties gave impetus to a study recently undertaken to investigate the phenomenon. The aim of the study was to gain meaningful insight into the phenomenon by exploring patterns in the spatial distribution of the problematic auctioned properties. The study utilized a dataset of 29,704 residential properties offered for auction over the period of 2005 to 2009 in Selangor and Kuala Lumpur, the two most developed states of Malaysia. With the help of a GIS, spatial patterns were explored and were found to exist in ways that allowed certain interpretations to be made toward understanding what had happened and why. We found certain localities to be more prone to the incidences of problematic properties and, in this paper, offered some explanations why. As the next step forward, we suggest that a model for predicting the incidence of problematic properties be developed.